Neuroblastoma in Spain: Linking the national clinical database and epidemiological registries – A study by the Joint Action on Rare Cancers. (June 2022) - Cañete, Adela; Peris-Bonet, Rafael; Capocaccia, Riccardo; Pardo-Romaguera, Elena; Segura, Vanessa; Muñoz-López, Ana; Fernández-Teijeiro, Ana; Galceran-Padros, Jaume; Gatta, Gemma; ,; Almazán, F; Benito, AI; et al.
Abstract: Purpose: Linkage between clinical databases and population-based cancer registries may serve to evaluate European Reference Networks' (ERNs) activity, by monitoring the proportion of patients benefiting from these and their impact on survival at a population level. To test this, a study targeting neuroblastoma (Nb) was conducted in Spain by the European Joint Action on Rare Cancers. Material and methods: Subjects: Nb cases, incident 1999–2017, aged < 15 years. Linkage included: Spanish Neuroblastoma Clinical Database (NbCDB) (1217 cases); Spanish Registry of Childhood Tumours (RETI) (1514 cases); and 10 regional population-based registries (RPBCRs) which cover 33% of the childhood population (332 cases). Linkage was semiautomatic. We estimated completeness, incidence, contribution, deficit, and 5-year survival in the databases and specific subsets. Results: National completeness estimates for RETI and NbCDB were 91% and 72% respectively, using the Spanish RPBCRs on International Incidence of Childhood Cancer (https://iicc.iarc.fr/) as reference. RPBCRs' specific contribution was 1.6%. Linkage required manual crossover in 54% of the semiautomatic matches. Five-year survival was 74% (0–14 years) and 90% (0–18 months). Conclusions: All three databases were incomplete as regards Spain as a whole and should therefore be combined to achieve full childhood cancer registration. A unique personal patient identifier could facilitate such linkage. Most children have access to Nb clinical trials. Consolidated interconnections between the national registry and clinical registries (including ERNs and paediatric oncology clinical groups) should be established to evaluate outcomes. Highlights: A unique personal patient identifier common to all health databases is needed Semi-automatic linkage is feasible but laborious Clinical database showed underreporting when compared to epidemiological registries Clinical databases and epidemiological registries are complementary Stable interconnection between registries and clinical databases is needed